Rapid assessment of macrobenthic invertebrates in the mangrove forests of Barangay Cogon, Palo, Leyte, Philippines. - Dimakiling, Ernest R.; Parilla, Richard B. (2023)
Mangroves are natural barriers that offer various ecological services, however, they greatly suffer the effects of natural disasters and other environmental factors. Assessing mangrove-associated flora and fauna such as macrobenthic invertebrates may determine its current habitat status. I relation, this study aimed to determine the macrobenthic invertebrate composition in the mangrove forests of Barangay Cogon, Palo, Leyte, Philippines. The study area was stratified into two stations, Station 1 (mainland) and Station 2 (barrier island). Measurement of selected physico-chemical parameters and collection of macrobenthic invertebrates was conducted in February 2022. Station 1 showed higher species relative abundance and density than Station 2. For biodiversity indices, Station 1 showed higher species richness and diversity than Station 2 however, Station 2 showed higher species evenness and dominance than Station 1. The similarity index for both stations is 70.97%. Though the measured temperatures and pH were within the range suitable for macrobenthic invertebrates, factors that may affect the presence and abundance of these organisms in the study area may include water currents from tidal creek, natural barriers, anthropogenic disturbance, and predation. In general, the mangrove forest in Brgy. Cogon, Palo, Leyte, Philippines exhibited satisfactory environmental conditions for macrobenthic invertebrates to thrive however, implementation of more effective sampling methods and techniques, as well as longer sampling durations, is highly recommended.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.